Water, sanitation, and hygiene as a priority intervention for stunting in under-five children in northwest Ethiopia: a community-based cross-sectional study - Ayechew Ademas; Metadel Adane; Awoke Keleb; Gete Berihun; Getu Tesfaw (BMC, 2021)
Abstract Background Stunting was a significant public health problem for under-five in developing countries including Ethiopia. Globally, it was estimated 21.9% or 149 million (81.7 million in Asia and 58.8 million in Africa) under-five children stunted in 2018. In East Africa, 24 million are stunted which is the highest-burden from African regions. Hence, this study aimed to assess the prevalence of stunting and its association with Water Sanitation and Hygiene (WASH) in northwestern Ethiopia. Method A community-based cross-sectional study design was conducted among 630 participants from December to mid-January 2019. From five kebeles, two were selected by a simple random sampling technique for the study. To reach study participants a systematic sampling technique was used. Data were collected by using an observational checklist, pretested questionnaire, and anthropometric measurement. Anthropometric indicator, height-for-age was determined using the current World Health Organization (WHO) growth standards. Multivariable logistic regression analysis was computed to analyze the data. From the multivariable analysis the Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) and P-value < 0.05 were used to declare statistical significance. Result The prevalence of stunting among under-five children was 35.6% (95%CI; 31.9-39.5%). The result from this study showed that having illiterate father and mother, give birth before marriage (single), large family size, short maternal height, unimproved drinking water source, unimproved sanitation, poor hygienic practice, having diarrhea in the previous 2 weeks before the data collection, method of child feeding, age at which complementary feeding started, frequency of feeding, not deworming and mothers who had antenatal care visit of fewer than three times were statistically associated with stunting. Conclusion In this study, stunting was an important public health problem among under-five children. It remains the same as the national average prevalence of Ethiopia. To alleviate this problem proper family planning utilization, good dietary intake, maternal and paternal education, and WASH interventions are critical.